CITRA PEREMPUAN DALAM CERITA RAKYAT WAINDHO-INDHODHIYU PADA MASYARAKAT WAKATOBI - Ansor Putra (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2018)
One of the ways to understand the socio-cultural life of the people can be done through its folklore. In this study, it is aming at descrining how the women images in Wakatobi society through the characterization of Waindho-Indhodhiyu main character.This study used descriptive method by applying crtical feminisms approach. The results of this study indicates that the image of women in Waindho-Indhodhiyu folklore is viewed from the aspect of her self-image known to Waindho-Indhodhiyu as a character of adult women who is considered as aubordinate of man. They are marginalized as weaker than men because of patriarchal culture. While based on its social image, the character of Waindho-Indhodhiyu is a character who has concern and pay attention to her family. Waindho-Indhodhiyu is also a character who always teaches her children about the good values and morals of life. On the other hand, the image of women in Waindho-Indhodhiyu folklore is a character who represents women's resistance to male domination. Keywords: folklore, feminist literary criticism, women